Microsaccades and Exploratory Saccades in a Naturalistic Environment - Simone Benedetto; Marco Pedrotti; Bruce Bridgeman (Bern Open Publishing, 2011)
Microsaccades, small saccadic eye movements made during fixation, might accompany shifts of visual attention, serve to refresh the retinal image, or have some other function. We tested the relative importance of these functions by recording exploratory saccades and microsaccades with a free head during a lane-change task in a simulated driving environment, accompanied by a simultaneous visual search task in which drivers searched for a target among similar distractors on a panel to the driver's right where an electronic display would normally be located. After training, observers performed a baseline run with the lane-change task only, followed by four dual-task runs and a final control run. In the dual-task condition, where more visual attention shifts occur, we found a significantly increased frequency of microsaccades along with an even larger increase in frequency of large exploratory saccades. However the proportion of microsaccades significantly decreased in the dual task, consistent with the idea of a common neurological origin for microsaccades and exploratory saccades.